HIRING DISCRIMINATION (WEIS ALLEGATIONS) - MARCOTULLIO, RICHARD (Tufts Archival Research Center, 2007)
Missing Attachments; Memorandum from R.J. Reynolds vice-president regarding hiring discrimination. Refers to an unenclosed article written by Professor Lewis C. Solomon on smoker's rights issues in the workplace. Details circulation and publication of the article and the intended audience.